Phenolic Contents and Antioxidant Potential of Crataegus Fruits Grown in Tunisia as Determined by DPPH, FRAP, and β-Carotene/Linoleic Acid Assay - Farouk Mraihi; Mohamed Journi; Jamila Kalthoum Chérif; Munevver Sokmen; Atalay Sokmen; Malika Trabelsi-Ayadi (Journal of Chemistry)
Crataegus fruit is one of most important fruits in Tunisian flora. Some fruits of this genus are edible. This study was undertaken in order to examine the benefits of these fruits in human health and their composition of antioxidants including total polyphenol, flavonoids, proanthocyanidins content, and total anthocyanins. The antioxidative properties of the ultrasonic methanolic extract were assessed by different in vitro methods such as the FRAP, DPPH, and β-carotene/linoleic acid assay. We concluded that peel fraction of red fruits possessed relatively high antioxidant activity and might be a rich source of natural antioxidants in comparison with the pulp and seed fruit extract. The results also showed that hawthorn yellow fruit presents lower amounts of phenolic content, absence of anthocyanins, and less antioxidant capacity. Most of peel and seed fractions were stronger than the pulp fractions in antioxidant activity based on their DPPH IC50, FRAP values, and results of β-carotene/linoleic acid. The total phenolic compounds contents were also highly correlated with the DPPH method and the FRAP assay.